a Pengaruh Model Pembelajaran Berbasis Masalah terhadap Kemampuan Menganalisis Karya Ilmiah pada Siswa Kelas XI SMA Negeri 4 Kota Bengkulu - Aulia, Vira; Noermanzah, Noermanzah; Utomo, Padi (UNIB Press, 2025)
The purpose of this study is to determine the influence of problem-based learning models on the ability to analyze scientific work in grade XI students of SMA Negeri 4 Kota Bengkulu. This research uses a quantitative approach with pseudo-experimental methods. The design used is one group pretest-posttest design. The population of this study was all grade XI students of SMA Negeri 4 Kota Bengkulu with a sample using random sampling, namely class XI MIPA 1 totaling 33 students. Data collection techniques use essay test techniques. Data analysis techniques by means of normality tests using the Shapiro-Wilk test, homogeneity tests using the f test, and paired samples tests. Based on the results of the study, a pretest score was obtained with an average of 44.18 and a posttest score was obtained with an average of 65.69. In the application of the problem-based learning model has 5 learning steps, namely orienting students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting work, and analyzing and evaluating the problem-solving process. The results showed that there is an influence of problem-based learning models on the ability to analyze scientific papers. This is evidenced by the results of the t,T-count test. > ,T-table. , then Ho was rejected which means that there is an influence of problem-based learning models on the ability to analyze scientific papers.